Applicability of Traps for Collecting Mosquito Immatures (Diptera: Culicidae) for Entomological Surveillance of Arbovirus Vectors in a Remnant of the Atlantic Forest, Rio de Janeiro State, Brazil - Rayane Dias; Cecilia Ferreira de Mello; Shayenne Olsson Freitas Silva; Hélcio Reinaldo Gil-Santana; Ana Laura Carbajal-de-la-Fuente; Jeronimo Alencar (Tropical Medicine and Infectious Disease, 2024)
Diverse larval habitats significantly influence female mosquito oviposition. Utilizing traps that simulate these habitats is helpful in the study of the bioecology and characteristics of pathogen-transmitting species during oviposition. This study evaluated the feasibility of different traps in natural environments by comparing sampling methods and detecting the oviposition of epidemiologically important mosquitoes, with emphasis on Haemagogus species, in a fragment of the Atlantic Forest in Silva Jardim, Rio de Janeiro State, Brazil. Monthly collections were conducted from March 2021 to October 2023 using four types of traps: plastic containers, tires, bamboo, and sapucaia. Immatures were collected from these traps using a pipette, placed in plastic bags, and transported to the laboratory. Tire was the most efficient trap, showing the highest mosquito abundance (n = 1239) and number of species (S = 11). Conversely, the plastic container trap exhibited the lowest diversity (H = 0.43), with only two species and a low mosquito abundance (n = 26). The bamboo trap captured six species and recorded the second-highest diversity index (H = 1.04), while the sapucaia trap captured five species and had the third-highest diversity index (H = 0.91). Of the total immatures collected, 1817 reached adulthood, comprising 13 species, two of which are vectors of the sylvatic yellow fever virus: Haemagogus leucocelaenus and Haemagogus janthinomys. In conclusion, detecting key vectors of the sylvatic yellow fever virus in Brazil highlights the need for ongoing entomological and epidemiological surveillance in the study area and its vicinity. These efforts are crucial for monitoring vector presence and activity, identifying potential transmission hotspots, and devising effective control and prevention strategies.